THE STUDENT’S PERCEPTION OF AMERICAN CAMPAIGN SPEECH AT THE PRESIDENT ELECTION IN 2024 - Eripuddin; Rahayu, Pipit (English Study Program University of Pasir Pengaraian, 2024)
The speakers’ utterance should be interpreted effectively to get the correct information. The purpose of this research was to find out the type of speech act of the US presidential candidate in 2024. This research was descriptive qualitative. The data of this research were primer and seconder data. The instrumentation of this research was the documentation. The data were collected by searching and interpreting the script of speech script. The data were analyzed by using Searle's theory ( 2012 ); speech act approach. The result of the research shows that the speaker's messages points to persuade and convince the society to choose them. The speakers try to point the truth of the idea, promote the promises, convince the ideas and represent the act to follow the speakers’ attention. Thus, many value and information are declared to the hearers.